(untitled) (Economic and Political Thought, 2018)
The aim of the article is to present the origin of the Polish-German Treaty of Good Neighbourship and Friendly Cooperation of 17 June 1991 and its significance for the process of reconciliation and development of versatile cooperation between Poland and Germany in the context of the present migration crisis in Europe. The author formulates a few interesting theses and tries to answer many questions concerning Polish-German relations in the period 1989–2018 and their conditions and prospects. Over the last two years, Polish-German relations, especially political ones, have considerably deteriorated. The international situation in Europe has also become more complicated. One of the reasons of the situation is the immigration crisis resulting from a massive influx of people from the Middle East and North Africa. The immigration crisis has divided the European Union and has affected relations between its Member States, including Polish-German relations.